Answer:
m=-2
Step-by-step explanation:
m=y2-y1/x2-x1
m=-2-8/3-(-2)
m=-2-8/3+2
m=-10/5
m=-2
Answer:
x=(2,-5.3)
Step-by-step explanation:
Hope this helps
Wouldn't it be 1? Because any number to the zero post power is 1?
The sides of a triangle must satisfy the triangle inequality, which states the sum of the lengths of any two sides is strictly greater than the length of the remaining side.
We really only have to check if the sum of the two smaller sides exceeds the largest side.
A. 5+6>7, ok
B. 6+6>10, ok
C. 7+7=14 Not ok, this is a degenerate triangle not a real triangle
D. 4+6>8 ok
Answer: C
Answer:
B
Step-by-step explanation:
The solution is the point of intersection of the 2 lines
The lines intersect at (- 3, - 4 ), then
f(x) = g(x) has solution x = - 3